Influence of Mercury's Exosphere on the Structure of the Magnetosphere. Issue 7 (15th July 2020) - Exner, Willi; Simon, Sven; Heyner, Daniel; Motschmann, Uwe
Abstract: Mercury is embedded in a tenuous and highly anisotropic sodium exosphere, generated mainly by plasma‐surface interactions. The absolute values of the sodium ion density are still under debate. Observations by MESSENGER's Fast Imaging Plasma Spectrometer (FIPS) instrument suggest the density of exospheric ions to be several orders of magnitude lower than the upstream solar wind density, indicating that the sodium exosphere has no substantial influence on the magnetospheric current systems. However, MESSENGER magnetic field observations of field line resonances revealed sodium ion densities comparable to the upstream solar wind density. To investigate how a dense exosphere would affect the current systems within Mercury's magnetosphere, we apply an established hybrid (kinetic ions, fluid electrons) model and conduct multiple model runs with gradually increasing exospheric density, ranging from no sodium ions at all to comet‐like configurations. We demonstrate how a sufficiently dense exosphere leads to self‐shielding of the sodium ion population from the ambient electric field and a significant inflation and symmetrization of Mercury's magnetosphere, which is decreasingly affected by the dipole offset. Once the sodium ion density is sufficiently high, Region 2 field‐aligned currents emerge close to the planet. The modeled Region 2 currents are located below the orbit of MESSENGER, thereby providing a possible explanation for the absence of these currents in observations. The sodium exosphere also closes a significant fraction of the Region 1 currents through Pedersen and Hall currents before the "guiding" magnetic field lines even reach the planetary surface. The modeled sodium ion and solar wind densities agree well with observations. Key Points: A hybrid model is applied to study the influence of Mercury's sodium exosphere on the currents in the magnetosphere A dense sodium exosphere based on Gamborino et al. (2019) partially closes Region 1 currents before they reach the dayside surface With a dense sodium exosphere included, Region 2 currents can form below the altitude of MESSENGER's orbit